Changing epidemiology of skin cancers in southwestern Nigeria. (2006)
Introduction: The incidence of some skin cancers is on the rise in Caucasians1. There is also an observed increase in the diagnosis of Basal Cell Carcinoma in blacks. This study evaluated the Pattern of Skin Cancers in Southwestern Nigeria and compared the trends with what obtained three decades earlier. Methods: A review of 494 cases of skin malignancies recorded at the National cancer registry, Ibadan, Nigeria between January 1981 and December 2000 was carried out. The proportion observed was compared with a similar study carried out thirty years earlier. Results: The commonest lesion recorded was squamous cell carcinoma 40.5%. Malignant Melanoma was 25.1%, Dermatofibrosarcoma Protuberance 9.5%, Kaposi’s Sarcoma 8.3% and Basal Cell Carcinoma 6.7%. There was an observed decline in the proportion of Squamous Cell Carcinoma and an increase in the proportion of Basal Cell Carcinoma. Conclusion: There is a change in the incidence of skin cancers in Southwestern Nigeria.